Utilization of Library Collections to Meet User Needs In The Diplomacy Library - Rahmadhan, Mutiara (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
Libraries are organizations that provide information services, and should emphasize assessing the number of users served and the level of satisfaction. The library is a scientific institution that has main tasks related to science, education, research and development, with its scope of managing and storing information covering various sciences and technology. Utilization of collections in the Library Diplomacy is a way to utilize collections by filling out guest books, borrowing collections from the library, and reading in the library. The needs of users in utilizing important library collections to provide relevant and meaningful services. Provides a diverse collection to cover a wide range of interests, knowledge levels, and educational needs. Influences interest in visiting the library, both external and internal influences. This research is entitled